Preparation method of high-volume resistivity electrostatic chuck aluminum nitride ceramic disc

By utilizing doping and solid solution effects in aluminum nitride ceramic discs, the high-temperature volume resistivity is improved and the sintering temperature is reduced, and the problems of low volume resistivity and high sintering temperature in the prior art are solved, thus achieving high efficiency Electrical performance improvement and energy conservation.

CN119241252APending Publication Date: 2025-01-03JUNYUAN ELECTRONIC TECHNOLOGY (HAINING) CO LTD

Patent Information

Application Number
CN202411213586.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing aluminum nitride ceramic electrostatic suction cups have insufficient volume resistivity and high sintering temperature at high temperatures.

Method used

The mixture ball mill is used to use aluminum nitride powder, oxide dopants and organic additives, and sintered by dry pressure or casting, and doping and solid solution effects of the yttrium aluminate phase and the magnesium aluminum spinel phase. , adjust the charge balance and conduction channels, improve the volume resistivity of the ceramic, and reduce the sintering temperature through biaxial pressurized nitrogen hot press sintering.

Benefits of technology

It significantly improves the high-temperature volume resistivity of aluminum nitride ceramic disks, meets the requirements for the use of semiconductor-grade precision ceramic parts, and at the same time reduces the sintering temperature and reduces energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241252A_ABST
    Figure CN119241252A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-volume-resistivity electrostatic chuck aluminum nitride ceramic plate, and belongs to the technical field of electrostatic chucks, the method comprises the following steps: raw material preparation: aluminum nitride powder, an oxide dopant and an organic additive are used as raw materials, the oxide dopant comprises 0.1-1 wt% of SiO2, 0.1-1 wt% of TiO2, 0.1-5 wt% of Y2O3, 0.1-2 wt% of CaO, 0.1-2 wt% of MgO and 0.1-2 wt% of BaO, the organic additive is added into the aluminum nitride powder, and the organic additive is added into the aluminum nitride powder; the organic additives comprise a solvent, a dispersing agent and a binder; the raw materials are subjected to mixing and ball milling for 4-8 h through a planetary ball mill, the ball milling rotating speed is 350-450 r / min, and the ball milling temperature is 25-30 DEG C; forming: forming by adopting a dry pressing forming method or a tape casting forming method; glue discharging: the highest temperature of glue discharging is 500-600 DEG C; sintering: adopting double-shaft pressurized nitrogen hot pressed sintering, keeping the highest temperature of the ceramic body at 1600-1800 DEG C for 2-8 hours, and keeping the pressure at 5-30 Mpa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrostatic chucks, and in particular to a method for preparing an aluminum nitride ceramic disc of an electrostatic chuck with high volume resistivity. Background Art

[0002] The theoretical thermal conductivity of aluminum nitride is 320W / m·K. It is widely used as an anti-plasma material in semiconductor manufacturing equipment that requires uniform temperature distribution of silicon wafers: such as electrostatic chucks and heaters used in chemical vapor deposition (CVD), etching machines and other types of equipment. According to the definition of ITRS (International Technology Roadmap for Semiconductors), if the lithography node of silicon-based semiconductors shrinks to less than 10nm. Because the etching or deposition temperature increases with the growth of integration density, a dielectric with high resistivity is required to work at high temperature. AlN ceramic dielectrics have high resistivity and low dielectric loss at high temperature and high pressure. At this time, the volume resistivity ρv>109Ω·cm, the dielectric loss tanθ<0.2, T>500℃, and the aluminum nitride ceramic electrostatic chuck has better resistivity and thermal conductivity than alumina ceramic electrostatic chuck, and is widely used at home and abroad. However, if the volume resistivity of the ceramic needs to be further improved, various elements need to be added before the ceramic is formed. However, there are still problems with low volume resistivity, such as ρv<109Ω·cm when T=550℃, and high sintering temperature, such as the sintering temperature is higher than 1800℃. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a method for preparing an aluminum nitride ceramic disc with a high volume resistivity electrostatic chuck, which can improve the electrical properties of the aluminum nitride ceramic disc, especially the high-temperature volume resistivity.

[0004] In order to solve the above technical problems, the technical solution of the present invention is:

[0005] A method for preparing an aluminum nitride ceramic disc for an electrostatic chuck with high volume resistivity, the method comprising:

[0006] Raw material preparation: aluminum nitride powder, oxide dopant and organic additive are used as raw materials, wherein the oxide dopant includes 0.1-1wt% SiO2, 0.1-1wt% TiO2, 0.1-5wt% Y2O3, 0.1-2wt% CaO, 0.1-2wt% MgO and 0.1-2wt% BaO, and the organic additive is a solvent, a dispersant and a binder;

[0007] Mixing: Use a planetary ball mill to mix the above raw materials for 4 to 8 hours, the speed of the ball mill is 350 to 450 r / min, and the temperature of the ball mill is 25 to 30 ° C;

[0008] Molding: Dry pressing or tape casting is used for molding. The dry pressing method includes: spray granulation followed by dry pressing, wherein the added binder is 4-7wt% acrylic resin, D50 is 70-100um, and the dry pressing pressure is 5-15Mpa; tape casting laminate molding is used, wherein the binder is 8-13wt% acrylic resin, the viscosity is 10,000-25,000cp, the molding pressure is 5-15Mpa, and the molding temperature is 65-90°C;

[0009] Debinding: The maximum temperature of debinding is 500-600℃. The maximum temperature holding time of the ceramic green body formed by dry pressing is 2-4h, and the maximum temperature holding time of the ceramic green body formed by tape casting and lamination is 8-24h.

[0010] Sintering: Biaxial pressurized nitrogen hot pressing sintering is adopted, the highest temperature of the ceramic body is 1600-1800℃, the highest temperature holding time is 2-8h, and the pressure is 5-30Mpa; after the aluminum nitride ceramic disk is sintered, aluminum nitride is used as the main crystal phase, and the yttrium aluminate phase and magnesium aluminum spinel phase are used as secondary phases. However, doping +2-valent cations such as Mg / Ca / Ba in the yttrium aluminate phase will replace the +3-valent Y ions, resulting in a charge imbalance and generating oxygen ion vacancies. The oxygen vacancies can be used as conductive channels, thereby reducing the volume resistivity. In the yttrium aluminate phase, +4-valent cations such as Ti / Si dissolved in the yttrium aluminate phase will replace the +3-valent Al ions, thereby balancing the cation vacancies generated by the replacement of high-valent cations by low-valent cations, reducing the conductive pathways and thereby increasing the volume resistivity of the ceramic.

[0011] Preferably, the volume resistivity of the ceramic disk after sintering at 550°C is greater than or equal to 10 9 Ω·cm, volume resistivity at 600℃ is greater than or equal to 5*10 8 Ω·cm.

[0012] Preferably, after sintering, the Ti / Mg value of the ceramic disk is less than or equal to 0.3, and the Y / Mg value is greater than or equal to 5.

[0013] Preferably, the density of the ceramic disc after sintering is 3.27-3.33 g / cm 3 , the average particle size is 1.5 to 4 microns.

[0014] Preferably, the dielectric constant of the ceramic disk after sintering at 500° C. is 10-20, and the dielectric loss at 500° C. is less than 0.15.

[0015] The above technical solution has the following beneficial effects:

[0016] The electrical properties of the aluminum nitride ceramic disc for electrostatic chucks prepared by the technical solution of the present application, especially the high-temperature volume resistivity, are significantly improved, meeting the use requirements of semiconductor-grade precision ceramic parts;

[0017] The sintering temperature of the aluminum nitride ceramic disc for the electrostatic chuck prepared by the method of the present application is 1600-1800°C, while the sintering temperature of general aluminum nitride ceramics is above 1800°C, which reduces the sintering temperature and significantly reduces energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a schematic diagram of the sintering process curve of the aluminum nitride ceramic disc of the electrostatic chuck with high volume resistivity of the present invention;

[0019] Figure 2 This is a SEM image of the aluminum nitride ceramic disc of the electrostatic chuck with high volume resistivity of the present invention;

[0020] Figure 3 The element distribution diagram of the aluminum nitride ceramic disc of the high volume resistivity electrostatic chuck of the present invention;

[0021] Figure 4 This is an element spectrum diagram of the aluminum nitride ceramic disk of the high volume resistivity electrostatic chuck of the present invention;

[0022] Figure 5 This is a grain size distribution diagram of the aluminum nitride ceramic disk of the high volume resistivity electrostatic chuck of the present invention;

[0023] Figure 6 A graph showing the relationship between the Ti / Mg mass ratio and the resistivity of the aluminum nitride ceramic disc of the high volume resistivity electrostatic chuck of the present invention;

[0024] Figure 7 This is a relationship diagram between the Y / Mg mass ratio and resistivity of the aluminum nitride ceramic disk of the high volume resistivity electrostatic chuck of the present invention. DETAILED DESCRIPTION

[0025] The specific embodiments of the present invention are further described below in conjunction with the accompanying drawings. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0026] Example 1

[0027] A method for preparing an aluminum nitride ceramic disc for an electrostatic chuck with high volume resistivity, the method comprising:

[0028] Raw material preparation: aluminum nitride powder, oxide dopant and organic additive are used as raw materials, wherein the oxide dopant includes 0.1-1wt% SiO2, 0.1-1wt% TiO2, 0.1-5wt% Y2O3, 0.1-2wt% CaO, 0.1-2wt% MgO and 0.1-2wt% BaO, and the organic additive is a solvent, a dispersant and a binder;

[0029] Mixing: Use a planetary ball mill to mix the above raw materials for 4 to 8 hours, the speed of the ball mill is 350 to 450 r / min, and the temperature of the ball mill is 25 to 30 ° C;

[0030] Molding: Dry pressing or tape casting is used for molding. The dry pressing method includes: spray granulation followed by dry pressing, wherein the added binder is 4-7wt% acrylic resin, D50 is 70-100um, and the dry pressing pressure is 5-15Mpa; tape casting laminate molding is used, wherein the binder is 8-13wt% acrylic resin, the viscosity is 10,000-25,000cp, the molding pressure is 5-15Mpa, and the molding temperature is 65-90°C;

[0031] Debinding: The maximum temperature of debinding is 500-600℃. The maximum temperature holding time of the ceramic green body formed by dry pressing is 2-4h, and the maximum temperature holding time of the ceramic green body formed by tape casting and lamination is 8-24h.

[0032] Sintering: Biaxial pressurized nitrogen hot pressing sintering is adopted, the highest temperature of the ceramic body is 1600-1800℃, the highest temperature holding time is 2-8h, and the pressure is 5-30Mpa; after the aluminum nitride ceramic disc is sintered, aluminum nitride is used as the main crystal phase, and yttrium aluminate phase (Y4Al2O9 (YAM), YAlO3 (YAL)) and magnesium aluminum spinel phase (MgAl2O4) are used as secondary phases. However, doping Mg / Ca / Ba and other +2-valent cations in the yttrium aluminate phase will replace +3-valent Y ions, resulting in a charge imbalance and generating oxygen ion vacancies. Oxygen vacancies can be used as conductive channels, thereby reducing the volume resistivity. However, if +4-valent cations such as Ti / Si are dissolved in the yttrium aluminate phase, they will replace +3-valent Al ions, thereby balancing the cation vacancies generated by the replacement of high-valent cations by low-valent cations, reducing the conductive pathways and thus increasing the volume resistivity of the ceramic;

[0033] refer to Figure 1 , is a sintering system curve of the aluminum nitride ceramic disc with high volume resistivity electrostatic chuck of the present invention, the highest sintering temperature is between 1600℃ and 1800℃, which is lower than the prior art, and the pressure is maintained at 5-20Mpa during sintering;

[0034] refer to Figure 2 , Figure 3 , which is the SEM image and element distribution diagram of the aluminum nitride ceramic disk of the electrostatic chuck with high volume resistivity of the present invention. The yttrium aluminate phase and the magnesium aluminum spinel phase need to be distributed in a dotted manner between the AlN grains, and cannot be distributed in a network, otherwise a conductive path will be formed to reduce the volume resistivity of the ceramic;

[0035] refer to Figure 4 , Figure 4 This is an element spectrum diagram of the aluminum nitride ceramic disk of the high volume resistivity electrostatic chuck of the present invention;

[0036] refer to Figure 5 , is a grain size distribution diagram of the aluminum nitride ceramic disk of the electrostatic chuck with high volume resistivity of the present invention, the AlN grain is controlled between 1.5um and 4um, and the smaller the better, and the resistivity is improved by increasing the content of high resistance grain boundaries;

[0037] The volume resistivity of the aluminum nitride ceramic disc sintered by the above method at 550°C is greater than or equal to 10 9 Ω·cm, volume resistivity at 600℃ is greater than or equal to 5*10 8 Ω·cm;

[0038] The Ti / Mg value of the ceramic disc after sintering is less than or equal to 0.3, reference Figure 6 , a relationship diagram between the Ti / Mg mass ratio and the resistivity of the aluminum nitride ceramic disc of the high volume resistivity electrostatic chuck of the present invention;

[0039] The value of Y / Mg is greater than or equal to 5, refer to Figure 7 , is a relationship diagram between the Y / Mg mass ratio and the resistivity of the aluminum nitride ceramic disc of the high volume resistivity electrostatic chuck of the present invention;

[0040] The density of the sintered ceramic disc is 3.27-3.33 g / cm 3 , the average particle size is 1.5 to 4 microns;

[0041] The dielectric constant of the ceramic disk after sintering at 500°C is 10-20, and the dielectric loss at 500°C is less than 0.15;

[0042] The electrical properties of the aluminum nitride ceramic disc for electrostatic chuck obtained by the above preparation method, especially the high-temperature volume resistivity, are significantly improved, meeting the use requirements of semiconductor-grade precision ceramic parts;

[0043] The sintering temperature of the aluminum nitride ceramic disc in the technical solution of the present application is 1600-1800° C., while the sintering temperature of general aluminum nitride ceramics is above 1800° C., which reduces the sintering temperature, significantly reduces energy consumption, and reduces sintering requirements.

[0044] Example 2

[0045] A method for preparing an aluminum nitride ceramic disc for an electrostatic chuck with high volume resistivity, comprising:

[0046] Raw material preparation: aluminum nitride powder, oxide dopants and organic additives are used as raw materials, wherein the oxide dopants include 0.1wt% SiO2, 0.1wt% TiO2, 0.1wt% Y2O3, 0.1wt% CaO, 0.1wt% MgO and 0.1wt% BaO, and the organic additives are solvents, dispersants and binders;

[0047] Mixing: The above raw materials were mixed and ball-milled in a planetary ball mill for 4 hours, the speed of the ball mill was 350 r / min, and the temperature of the ball mill was 25°C;

[0048] Molding: Dry pressing or tape casting is used for molding. The dry pressing method includes: spray granulation followed by dry pressing, wherein the added binder is 4wt% acrylic resin, D50 is 70um, and the dry pressing pressure is 5Mpa; tape casting lamination molding is used, wherein the binder is 8wt% acrylic resin, the viscosity is 10,000cp, the molding pressure is 5Mpa, and the molding temperature is 65°C;

[0049] Debinding: The maximum temperature of debinding is 500℃. The maximum temperature holding time of the ceramic green body formed by dry pressing is 2h, and the maximum temperature holding time of the ceramic green body formed by tape casting and lamination is 8h.

[0050] Sintering: Biaxial pressurized nitrogen hot pressing sintering is adopted, the highest temperature of the ceramic body is 1600℃, the highest temperature holding time is 2h, and the pressure is 5Mpa; after the aluminum nitride ceramic disc is sintered, aluminum nitride is used as the main crystal phase, and the yttrium aluminate phase (Y4Al2O9 (YAM), YAlO3 (YAL)) and magnesium aluminum spinel phase (MgAl2O4) are used as secondary phases. However, doping Mg / Ca / Ba and other +2-valent cations in the yttrium aluminate phase will replace the +3-valent Y ions, resulting in a charge imbalance and generating oxygen ion vacancies. Oxygen vacancies can be used as conductive channels, resulting in a decrease in volume resistivity. However, if +4-valent cations such as Ti / Si are dissolved in the yttrium aluminate phase, they will replace the +3-valent Al ions, thereby balancing the cation vacancies generated by the replacement of high-valent cations by low-valent cations, reducing the conductive pathways and thus increasing the volume resistivity of the ceramic;

[0051] The volume resistivity of the aluminum nitride ceramic disc sintered by the above method at 550°C is greater than or equal to 10 9 Ω·cm, volume resistivity at 600℃ is greater than or equal to 5*10 8 Ω·cm;

[0052] After the ceramic disk is sintered, the Ti / Mg value is less than or equal to 0.3, and the Y / Mg value is greater than or equal to 5;

[0053] The density of the sintered ceramic disc is 3.27-3.33 g / cm 3 , the average particle size is 1.5 to 4 microns;

[0054] The dielectric constant of the ceramic disk after sintering at 500° C. is 10-20, and the dielectric loss at 500° C. is less than 0.15.

[0055] Example 3

[0056] A method for preparing an aluminum nitride ceramic disc for an electrostatic chuck with high volume resistivity, comprising:

[0057] Raw material preparation: aluminum nitride powder, oxide dopant and organic additive are used as raw materials, wherein the oxide dopant includes 1wt% SiO2, 1wt% TiO2, 5wt% Y2O3, 2wt% CaO, 2wt% MgO and 2wt% BaO, and the organic additive is solvent, dispersant and binder;

[0058] Mixing: The above raw materials were mixed and ball-milled for 8 hours using a planetary ball mill, the speed of the ball mill was 450 r / min, and the temperature of the ball mill was 30°C;

[0059] Molding: Dry pressing or tape casting is used for molding. The dry pressing method includes: spray granulation followed by dry pressing, wherein the added binder is 7wt% acrylic resin, D50 is 100um, and the dry pressing pressure is 15Mpa; tape casting laminate molding is used, wherein the binder is 13wt% acrylic resin, the viscosity is 25,000cp, the molding pressure is 15Mpa, and the molding temperature is 90°C;

[0060] Debinding: The maximum temperature of debinding is 600℃. The maximum temperature holding time of the ceramic green body formed by dry pressing is 4h, and the maximum temperature holding time of the ceramic green body formed by tape casting and lamination is 24h.

[0061] Sintering: Biaxial pressurized nitrogen hot pressing sintering is adopted, the highest temperature of the ceramic body is 1600-1800℃, the highest temperature holding time is 8h, and the pressure is 30Mpa; after the aluminum nitride ceramic disc is sintered, aluminum nitride is used as the main crystal phase, and yttrium aluminate phase (Y4Al2O9 (YAM), YAlO3 (YAL)) and magnesium aluminum spinel phase (MgAl2O4) are used as secondary phases. However, doping Mg / Ca / Ba and other +2-valent cations in the yttrium aluminate phase will replace +3-valent Y ions, resulting in a charge imbalance and generating oxygen ion vacancies. Oxygen vacancies can be used as conductive channels, thereby reducing the volume resistivity. However, if +4-valent cations such as Ti / Si are dissolved in the yttrium aluminate phase, they will replace +3-valent Al ions, thereby balancing the cation vacancies generated by the replacement of high-valent cations by low-valent cations, reducing the conductive pathways and thus increasing the volume resistivity of the ceramic;

[0062] The volume resistivity of the aluminum nitride ceramic disc sintered by the above method at 550°C is greater than or equal to 10 9 Ω·cm, volume resistivity at 600℃ is greater than or equal to 5*10 8 Ω·cm;

[0063] After the ceramic disk is sintered, the Ti / Mg value is less than or equal to 0.3, and the Y / Mg value is greater than or equal to 5;

[0064] The density of the sintered ceramic disc is 3.27-3.33 g / cm 3 , the average particle size is 1.5 to 4 microns;

[0065] The dielectric constant of the ceramic disk after sintering at 500° C. is 10-20, and the dielectric loss at 500° C. is less than 0.15.

[0066] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the scope of protection of the present invention.

Claims

1. A method for preparing an aluminum nitride ceramic disc for an electrostatic chuck with high volume resistivity, characterized in that: The method comprises: Raw material preparation: aluminum nitride powder, oxide dopant and organic additive are used as raw materials, wherein the oxide dopant includes 0.1-1wt% SiO2, 0.1-1wt% TiO2, 0.1-5wt% Y2O3, 0.1-2wt% CaO, 0.1-2wt% MgO and 0.1-2wt% BaO, and the organic additive is a solvent, a dispersant and a binder; Mixing: Use a planetary ball mill to mix the above raw materials for 4 to 8 hours, the speed of the ball mill is 350 to 450 r / min, and the temperature of the ball mill is 25 to 30 ° C; Molding: Dry pressing or tape casting is used for molding. The dry pressing method includes: spray granulation followed by dry pressing, wherein the added binder is 4-7wt% acrylic resin, D50 is 70-100um, and the dry pressing pressure is 5-15Mpa; tape casting laminate molding is used, wherein the binder is 8-13wt% acrylic resin, the viscosity is 10,000-25,000cp, the molding pressure is 5-15Mpa, and the molding temperature is 65-90°C; Debinding: The maximum temperature of debinding is 500-600℃. The maximum temperature holding time of the ceramic green body formed by dry pressing is 2-4h, and the maximum temperature holding time of the ceramic green body formed by tape casting and lamination is 8-24h. Sintering: Biaxial pressurized nitrogen hot pressing sintering is adopted, the highest temperature of the ceramic body is 1600-1800℃, the highest temperature holding time is 2-8h, and the pressure is 5-30Mpa; after the aluminum nitride ceramic disc is sintered, aluminum nitride is used as the main crystal phase, and the yttrium aluminate phase and magnesium aluminum spinel phase are used as secondary phases, wherein +2-valent cations such as Mg / Ca / Ba doped in the yttrium aluminate phase will replace the +3-valent Y ions, thereby resulting in a charge imbalance relationship and generating oxygen ion vacancies, which can be used as a conductive channel to reduce the volume resistivity, and +4-valent cations such as Ti / Si dissolved in the yttrium aluminate phase will replace the +3-valent Al ions, thereby balancing the cation vacancies generated by the replacement of high-valent cations by low-valent cations, reducing the conductive path and thereby improving the volume resistivity of the ceramic.

2. The method for preparing a high volume resistivity electrostatic chuck aluminum nitride ceramic disc according to claim 1, characterized in that: The volume resistivity of the ceramic disk after sintering at 550°C is greater than or equal to 10 9 Ω·cm, volume resistivity at 600℃ is greater than or equal to 5*10 8 Ω·cm.

3. The method for preparing a high volume resistivity electrostatic chuck aluminum nitride ceramic disc according to claim 1, characterized in that: After the ceramic disc is sintered, the Ti / Mg value is less than or equal to 0.3, and the Y / Mg value is greater than or equal to 5.

4. The method for preparing a high volume resistivity electrostatic chuck aluminum nitride ceramic disc according to claim 1, characterized in that: The density of the ceramic disc after sintering is 3.27-3.33 g / cm 3 , the average particle size is 1.5 to 4 microns.

5. The method for preparing a high volume resistivity electrostatic chuck aluminum nitride ceramic disc according to claim 1, characterized in that: After sintering, the dielectric constant of the ceramic disc at 500° C. is 10-20, and the dielectric loss at 500° C. is less than 0.15.

Citation Information

Patent Citations

  • Composite sintered body, electrostatic chuck member, and electrostatic chuck device

    CN110248910A

  • Aluminum nitride sintered compact for electrostatic chuck and method of forming the same

    JP2008127276A

  • Aluminum nitride sintered body, and electrostatic chuck

    JP2022052090A

  • High dense sintered body of aluminium nitride, methodfor preparing the same and member for manufacturingsemiconductor using the sintered body

    KR1020060111279A

  • Aluminum nitride ceramic, semiconductor manufacturing member, and manufacturing method for aluminum nitride ceramic

    US20060019817A1

Cited By

  • Aluminum nitride ceramic material and preparation method thereof

    CN121627414A